Consumer’s Buying Decision Behavior on Supplementary Food in Nonthaburi Province - สัมพัทธ์พงศ์, พรพิมล (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The purposes of this research were to; 1) study consumer’s buying decision behavior on supplementary food in Nonthaburi province, 2) study marketing mix factor affecting buying behavior on supplementary food of consumer in Nonthaburi province, and 3) compare marketing mix factor affecting buying behavior on supplementary food of consumer in Nonthaburi province with different personal factor. The samples were 400 consumers in Nonthaburi province. The research instrument was questionnaire. Descriptive statistics; frequency, percentage, mean, and standard deviation and inferential statistics; t-test, One-Way ANOVA were used in the data analysis. The results of research were as follows: 1) The consumers buy supplementary food one time per month. They spend 500 – 1,000 Baht at a time. The parents, relatives and friends’ opinion affecting buying behavior on supplementary food. The most of consumer buy supplementary food from leading department stores, shopping center or super center. 2) The mix marketing that affect to behavior on supplementary food in Nonthaburi province was at high level; product was at highest level, price, promotion, and place respectively. 3) The consumers with different gender had different marketing mix factor in product that affect to buying decision behavior on supplementary food, the consumers with different age had different marketing mix factor in product, price and promotion that affect to buying decision behavior on supplementary food, and the consumers with different occupation had different marketing mix factor in price and promotion that affect to buying decision behavior on supplementary food at .05 significant. The consumer with different educational background, income per month and marital status was found significantly difference in marketing mix factor.